IGF2 prevents dopaminergic neuronal loss and decreases intracellular alpha-synuclein accumulation in Parkinson’s disease models - Javiera Arcos; Felipe Grunenwald; Denisse Sepulveda; Carolina Jerez; Valentina Urbina; Tomas Huerta; Paulina Troncoso-Escudero; Daniel Tirado; Angela Perez; Rodrigo Diaz-Espinoza; Esteban Nova; Ulrich Kubitscheck; et al. (Cell Death Discovery, 2023)
Abstract Parkinson’s disease (PD) is the second most common late-onset neurodegenerative disease and the predominant cause of movement problems. PD is characterized by motor control impairment by extensive loss of dopaminergic neurons in the substantia nigra pars compacta (SNpc). This selective dopaminergic neuronal loss is in part triggered by intracellular protein inclusions called Lewy bodies, which are composed mainly of misfolded alpha-synuclein (α-syn) protein. We previously reported insulin-like growth factor 2 (IGF2) as a key protein downregulated in PD patients. Here we demonstrated that IGF2 treatment or IGF2 overexpression reduced the α-syn aggregates and their toxicity by IGF2 receptor (IGF2R) activation in cellular PD models. Also, we observed IGF2 and its interaction with IGF2R enhance the α-syn secretion. To determine the possible IGF2 neuroprotective effect in vivo we used a gene therapy approach in an idiopathic PD model based on α-syn preformed fibrils intracerebral injection. IGF2 gene therapy revealed a significantly preventing of motor impairment in idiopathic PD model. Moreover, IGF2 expression prevents dopaminergic neuronal loss in the SN together with a decrease in α-syn accumulation (phospho-α-syn levels) in the striatum and SN brain region. Furthermore, the IGF2 neuroprotective effect was associated with the prevention of synaptic spines loss in dopaminergic neurons in vivo. The possible mechanism of IGF2 in cell survival effect could be associated with the decrease of the intracellular accumulation of α-syn and the improvement of dopaminergic synaptic function. Our results identify to IGF2 as a relevant factor for the prevention of α-syn toxicity in both in vitro and preclinical PD models.